From Communicative Competence to Communication Proficiency: A Theoretical Study - Ahmed, Sabri (LPPM Universitas Advent Indonesia, 2023)
This study revisits the term ‘communicative competence’ and delves into its details. It presents briefly various models of communicative competence to show what has been written on this term, and then it introduces the term ‘communication proficiency’ as a broader term that includes all competencies and skills required for communication. It contributes to the field of research in applied linguistics as it helps scholars avoid the confusion associated with the term ‘communicative competence’ which is used differently by different scholars due to their different perceptions of the term ‘competence’. Competence has been perceived by some scholars as knowledge of language while others have perceived it as an overall ability that includes all what we need to function in real life and fulfill communicative needs.